Abolición vs continuidad del tráfico de esclavos. Una aproximación al tema desde las costas de África - Gómez Calderín, Sissy Indira; Fernández Carcassés, Manuel (CIICLA, Universidad de Costa Rica, 2021)
This article demonstrates that despite England's efforts to eliminate the African slave trade, the interests of America's slave elites promoted, in a clandestine manner, ways for certain quantities of slaves to continue to enter, especially United States, Brazil and Cuba. In the African territories, mechanisms were also used to circumvent the prohibitions, since the economy of the colonial enclaves, especially in the Kingdom  of Kongo and Angola, was still dependent on the trade of slaves, and it was difficult to quickly redirect it tos other activities. The same can be said of African societies of these regions, equally specialized in this inhuman activity, on which they depended. These factors conspired against a rapid extinction of slave trade and are discussed in this article through a collection of documents published in Angola. Bibliographic and documentary analysis methods were applied.